USE OF ADVANCED METHODS AND INNOVATIVE TECHNOLOGIES IN PEDAGOGY (ResearchJet Journal of Analysis and Inventions, 2021)
This article provides a number of theoretical and practical suggestions on how to organize and manage students' learning activities based on pedagogical methods and new innovative technologies.